On the interface boundary condition of Beavers, Joseph, and Saffman - Jäger, Willi; Mikelić, Andro (SIAM journal on applied mathematics, 2000)
We consider the laminar viscous channel flow over a porous surface. It is supposed, as in the experiment by Beavers and Joseph, that a uniform pressure gradient is maintained in the longitudinal direction in both the channel and the porous medium. After studying the corresponding boundary layers, we obtain rigorously Saffman's modification of the interface condition observed by Beavers and Joseph. It is valid when the pore size of the porous medium tends to zero. Furthermore, the coefficient in the law is determined through an auxiliary boundary-layer type problem.
Gesehen am 28.08.2018